Velikii kinemo : katalog sokhranivshikhsia igrovykh fil'mov Rossii, 1908-1919 - [sostaviteli, V. Ivanova ... et al.]. (Novoe literaturnoe obozrenie, 2002)
Includes bibliographical references and index.